2021
DOI: 10.1037/pha0000421
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of fixed and randomized price sequence on the alcohol purchase task.

Abstract: Factors influencing drug consumption can be effectively evaluated in the context of behavioral economic demand. Specifically, hypothetical purchase tasks (HPTs) allow for estimated drug consumption at a range of prices in which drug administration is not ethically or feasibly possible. With the marked increase of HPTs in behavioral research, understanding methodological influences on responding is paramount. One such methodological consideration is the price sequence, which can be presented in a fixed, ascendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Contrast comparisons indicate that the Random presentation produced significantly more failures of the Bounce criterion than the List presentation. These results are consistent with our hypothesis that Random would produce the greatest amount of failures of the unsystematic criteria and with previous reports of greater unsystematic data among random presentation of prices in an alcohol purchase task (Salzer et al, 2021). In terms of unsystematic data, these findings suggest that local effects, but not global effects, of price are sensitive to task presentation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Contrast comparisons indicate that the Random presentation produced significantly more failures of the Bounce criterion than the List presentation. These results are consistent with our hypothesis that Random would produce the greatest amount of failures of the unsystematic criteria and with previous reports of greater unsystematic data among random presentation of prices in an alcohol purchase task (Salzer et al, 2021). In terms of unsystematic data, these findings suggest that local effects, but not global effects, of price are sensitive to task presentation.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our hypothesis, Random produced a significantly lower R 2 than List and Ascending; List and Ascending were not significantly different. We observed that the ln(α) of Random was significantly lower than both List and Ascending (i.e., more inelastic), consistent with Salzer et al (2021). Also consistent with these results, ln(O max ) was significantly higher in Random than in List, indicating a higher expenditure at price Pmax (Kaplan et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Demand was evaluated across 13 prices from $0.00 [free] to $11 USD, presented in an ascending order (full price range: Free, $0.01, $0.05, $0.13, $0.25, $0.50, $1, $2, $3, $4, $5, $6, $11/drink). An ascending price sequence was used given evidence indicating similar patterns of response for ascending and randomized price sequences, but with higher systematic data rates for ascending sequences (Amlung & Mackillop, 2012; Salzer et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Roma et al (2016) provide a general set of guidelines for developing a novel price sequence (see also Reed et al, 2014). With respect to consideration over price sequencing, replicated research indicates little difference in quality or reliability of responding when prices are presented in ascending, descending, or randomized sequences (e.g., Salzer et al, 2021). Although the field would surely benefit from more research to arrive at a definite recommendation, current thinking lends to employing a price sequence that most logically fits with the commodity and framing in question.…”
Section: Pricingmentioning
confidence: 99%